Official dollarisation/euroisation - motives, features and policy implications of current cases - Adalbert Winkler; Francesco Mazzaferro; Carolin Nerlich; Christian Thimann (European Central Bank (ECB), 2004)
Official and unilateral dollarisation/euroisation has become a common policy advice for emerging market economies. Against this background, the paper provides a comprehensive review of all the main cases of dollarisation/euroisation, analysing motives, features and policy implications of this exchange rate regime. The main results are that policies fostering integration with the anchor country, in particular fiscal transfers, tourism and offshore finance, have been crucial in supporting the exchange rate regime. To this end, most dollarised/euroised countries have exploited advantages that are largely prior to the choice of exchange rate regime, namely their small size, geographic proximity to the anchor country, and politically dependent status. Thus, recommending dollarisation/euroisation irrespective of countries' ex ante degree of integration with the potential anchor country seems to bear considerable risks, as dollarisation/euroisation does not seem to be a straightforward substitute for integration.
Keywords: 330; Währungssubstitution; Euro; US-Dollar; Optimaler Währungsraum; Welt